The Relationship Between Consumer Legal Literacy Level And Dispute Resolution Of Buy Now Pay Later Service - Maulidiana, Lina; Renaldy, Rendy; Yoesry, Erni (PT. Anagata Sembagi Education, 2025)
This study examines the relationship between consumers' level of legal literacy and the effectiveness of dispute resolution in Buy Now Pay Later (BNPL) services in Indonesia. The rapid growth of BNPL has expanded financial access but also generated legal issues such as unilateral contracts, personal data breaches, and unethical debt collection practices. Employing a normative juridical approach, this research analyzes relevant legislation, legal doctrines, and scholarly works, including Law No. 8 of 1999 on Consumer Protection, Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector, Law No. 27 of 2022 on Personal Data Protection, and OJK Regulation No. 22 of 2023. The findings reveal that the lack of consumer legal literacy is a major factor hindering effective dispute resolution, despite the existence of adequate regulatory frameworks. A synergistic approach combining regulatory reform and digital legal-literacy empowerment is essential to help consumers understand their rights, obligations, and available redress mechanisms. Strengthening legal literacy will enhance consumers' bargaining power and promote a fairer, more transparent dispute-resolution system in Indonesia's digital financial sector.